Cytotoxic Effects of Five Species of Inula Against Some Tumor Cell Lines: Cytotoxicity of Inula spp - Mosaddegh, Mahmood; Naghibi, Farzaneh; H. Moghadam, Maryam; Naser Ostad, Syyed (Iranian Journal of Pharmaceutical Sciences, 2006)
The chloroform soluble fractions of ethanolic extracts of five Inula belonging to the Compositae family were evaluated for cytotoxic activity against five different cell lines including CACO2 (human colon adenocarcinoma), MCF7 (human breast adenocarcinoma), HEPG2 (human hepatocellular carcinoma), VERO (green African monkey kidney) and WEHI164 (balb c mouse fibrosarcoma). Cytotoxicity was assessed by MTT assay. Among these five species, Inula oculus christi, exhibited better cytotoxic effects.